Networking banana and plantain: Annual report 2002 - International Network for the Improvement of Banana and Plantain (2003)
INIBAP continues to expand its activities of coordinating and catalyzing Musa research through numerous partnerships across the world. However, only when our work is translated into benefits for smallholder banana farmers and improvement in livelihoods can we say our job is done.